2014
DOI: 10.1161/atvbaha.113.302335
|View full text |Cite
|
Sign up to set email alerts
|

Mice With Targeted Inactivation of Ppap2b in Endothelial and Hematopoietic Cells Display Enhanced Vascular Inflammation and Permeability

Abstract: Structured Abstract Objective Lipid phosphate phosphatase 3 (LPP3), encoded by the PPAP2B gene, is an integral membrane enzyme that dephosphorylates, and thereby terminates, the G-protein-coupled receptor-mediated signaling actions of lysophosphatidic acid (LPA) and sphingosine-1-phosphate (S1P). LPP3 is essential for normal vascular development in mice, and a common PPAP2B polymorphism is associated with increased risk of coronary artery disease in humans. Herein, we investigate the function of endothelial L… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
74
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 69 publications
(82 citation statements)
references
References 38 publications
(31 reference statements)
7
74
1
Order By: Relevance
“…8 Also, the inducible postnatal deletion of Ppap2b resulted in the disruption of endothelial barrier function and impaired angiogenesis. 9 Linking the loss of an LPA inactivating mechanism with endothelial cell activation or inflammation fits well with observations that decreasing LPA production or antagonizing its function are able to preserve barrier function. If an LPA-inactivating molecule is implicated in the endothelial cell response to flow, then its inhibition or downregulation should mimic the effects of disturbed or proatherogenic flow.…”
Section: Article See P E41supporting
confidence: 68%
“…8 Also, the inducible postnatal deletion of Ppap2b resulted in the disruption of endothelial barrier function and impaired angiogenesis. 9 Linking the loss of an LPA inactivating mechanism with endothelial cell activation or inflammation fits well with observations that decreasing LPA production or antagonizing its function are able to preserve barrier function. If an LPA-inactivating molecule is implicated in the endothelial cell response to flow, then its inhibition or downregulation should mimic the effects of disturbed or proatherogenic flow.…”
Section: Article See P E41supporting
confidence: 68%
“…This dynamic expression pattern of LPP3 in vasculature could refl ect its critical role during vascular development ( 106 ). A mouse model with conditional knockout of LPP3 in endothelial and hematopoietic cells shows similar defects in vasculogenesis and embryo death to those in mice with global knockout of LPP3 ( 107 ). The function of LPP3 knockout in endothelial cells of mice was revealed using a tamoxifen-inducible Cre-recombination.…”
Section: Lpp3 and The Vasculaturementioning
confidence: 99%
“…The function of LPP3 knockout in endothelial cells of mice was revealed using a tamoxifen-inducible Cre-recombination. LPP3 defi ciency in endothelial cells increases vascular permeability and enhanced sensitivity of infl ammation-induced vascular leak, which is restored by blocking LPA production or signals through LPA receptors ( 107 ). LPP3 also attenuates injuryinduced proliferation of carotid artery smooth muscle cells.…”
Section: Lpp3 and The Vasculaturementioning
confidence: 99%
“…Recently, phosphatidic acid phosphatase type 2B, an integral membrane protein known as lipid phosphate phosphatase-3 that inactivates LPA, was implicated in coronary artery disease by genome-wide association studies (43). LPA has been reported to promote endothelial permeability in culture models and mouse models with selective lipid phosphate phosphatase-3 deficiency (44,45). In addition, it was reported that the endothelial barrier function was restored by the pharmacological or genetic inhibition of either LPA production by the circulating ATX or of Gprotein-coupled receptor-dependent LPA signaling (45).…”
Section: Discussionmentioning
confidence: 99%